Soybean Oil Supplementation as a Source Conjugated Linoleic Acid (CLA) and Sweet Potato Leaves on the Pig LdL and HDL - I. S. Paembonan; N. Suthama; V. d. Yunianto (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2016)
This study aimed to determine whether provision of sweet potato leaves and soybean oil supplementation is able to lower low density lipoprotein (LDL) level and high density lipoprotein (HDL) level of blood. The number of pigs used in this study was 20 tails with average age of two months and initial body weight of 13.92±2.56 kg. Experimental diets were control diet - P0 (50% restaurant kitchen waste + 40% rice brand + 10% fish meal), P1 (85% of P0 + 15% sweet potato leaves with a 0.5% soybean oil supplementation), P2 (80% of P0 + 20% sweet potato leaves with a 0.5% soybean oil supplementation), P3 (85% of P0 + 15% sweet potato leaves with soybean oil supplementation 0.75%) and P4 (80% of P0 + sweet potato leaves 20 % with 0.75% soybean oil supplementation). Parematers observed were concentration of LDL and HDL in the blood of the experimental animal. Provision a combination of sweet potato leaves and soybean oil as a source of conjugated linoliec acid was significantly affect (P <0.05) the blood LDL and blood HDL levels of pigs. In conclusion, provision of sweet potato leaves supplemented soybean oil is capable of lowering LDL blood level and increasing the HDL blood level. Giving 15% sweet potato leaves supplemented with 0.5% soybean oil resulted in the lowest level of blood LDL and the hight level of blood HDL.